The Concept of Islamic Housing in Anticipating the Transmission of Covid-19 - Putri Suryandari (Research Synergy Foundation, 2022)
Large-scale changes around the world, are happening in all areas of life, due to the prolonged outbreak of the COVID-19 pandemic. At the same time, there is an adjustment in the pattern of life, as well as the pattern of our activities at home. In particular, more attention is paid to the spatial pattern of the house, to solve the problem of handling Covid patients, as well as to anticipate outbreaks for those who have not been infected, in dense urban areas. Islam as Rahmatan Lil Alamin is a guide for human life from ancient times to the end of time. So this study aims to find the concept of Islam according to the Qur'an and Hadith in anticipating the handling of COVID-19 patients and anticipating those who have not been infected. This study uses a descriptive method with a qualitative approach. Collaboration of Islamic conceptions in the arrangement of modern residential spaces that can be used as an alternative for anticipatory residential spatial planning against the Covid-19 outbreak.